Accounting theory : - Christensen, John A. (McGraw-Hill, 2003)
Accounting Theory, 1/e, by Christensen and Demski will cover both financial and managerial accounting theory with a strong emphasis on accounting information systems. It will be different from the other accounting theory textbooks available in that it will not focus solely on the FASB, its mission statement, and the rationale for specific FASB standards. This book will look at the challenges faced by accounting information users/preparers and the role accounting information systems play.